Competition during thermoregulation altered the body temperatures and hormone levels of lizards. (24th April 2017) - Rusch, Travis W.; Angilletta, Michael J.
Summary: Every organism must thermoregulate to maximize its performance, but competing organisms limit access to preferred microclimates. Such competition often creates hierarchies in which dominant individuals have more access to limited resources than subordinate individuals. To assess the costs of competition during thermoregulation, we measured thermoregulation, movement, and hormones of male lizards ( Sceloporus jarrovi ) when alone and when paired with a smaller or larger conspecific. Large males were 31% closer to the heat source when paired than when alone, resulting in a higher mean body temperature (35·7 vs. 33·9 °C). Conversely, small males were 40% farther from the heat source when paired, resulting in lower mean body temperature (32·1 vs. 33·6 °C). When paired, large and small males circulate 26 and 44% more corticosterone, respectively. Conversely, large males circulated 26% more testosterone when paired, whereas small males circulated 26% less testosterone. Both dominant and subordinate males incurred costs when paired, including poorer thermoregulation, more movement and greater physiological stress. Thus, competition for thermal resources should feature more prominently in ecological and evolutionary models of thermoregulation. A lay summary is available for this article. Abstract : Lay Summary